Hyperexcitability and Loss of Feedforward Inhibition Contribute to Aberrant Plasticity in the fmr1ko Amygdala - Cea-Del Rio, C (Society for Neuroscience, 2021)
Fragile X syndrome (FXS) is a neurodevelopmental disorder (NDD) characterized by intellectual disability, autism spectrum disorders (ASDs), and anxiety disorders. The disruption in the function of the FMR1 gene results in a range of alterations in cellular and synaptic function. Previous studies have identified dynamic alterations in inhibitory neurotransmission in early postnatal development in the amygdala of the mouse model of FXS. However, little is known about how these changes alter microcircuit development and plasticity in the lateral amygdala (LA). Using whole-cell patch clamp electrophysiology, we demonstrate that principal neurons (PNs) in the LA exhibit hyperexcitability with a concomitant increase in the synaptic strength of excitatory synapses in the BLA. Further, reduced feed-forward inhibition appears to enhance synaptic plasticity in the FXS amygdala. These results demonstrate that plasticity is enhanced in the amygdala of the juvenile Fmr1 knockout (KO) mouse and that E/I imbalance may underpin anxiety disorders commonly seen in FXS and ASDs. © 2021 Svalina et al.